Land use and turbine technology influences on wind potential in the United States. (15th May 2021) - Lopez, Anthony; Mai, Trieu; Lantz, Eric; Harrison-Atlas, Dylan; Williams, Travis; Maclaurin, Galen
Abstract: As clean energy ambitions have expanded, critically evaluating renewable energy supply has become increasingly important to the energy research community and stakeholders. This study examines the onshore wind resource potential for the conterminous United States and its sensitivity to siting constraints and turbine technology innovation. We compile localized regulatory information and use high-resolution data to present multiple siting regimes covering relatively constrained to unconstrained potentials. Our efforts reveal high sensitivity to these variables and sizable uncertainty in the overall wind energy resource potential. Specifically, we find that siting constraints may shift the total capacity available to commercial wind energy by 2.3–15.1 TW. Furthermore, our results illustrate that technology advancement could require larger setbacks from buildings and infrastructure, reducing the total available capacity potential by 20% relative to estimates using current technology, but that this reduction is largely offset by increased generation such that the net effect on generation is 1%. The observed sensitivity to and uncertainty resulting from the variables we analyze suggest there is value in continued study and development of increasingly sophisticated approaches to characterizing wind resource potential. Highlights: Wind energy potential is influenced by stringency of siting restrictions. Wind setback requirements pose the largest siting barrier to wind deployment. Wind turbine innovations can reduce the impact of stringent siting restrictions. Wind potential of the U.S. has large uncertainties, spanning 2.2–15.1 terawatts.